2020
DOI: 10.1177/1744629520961958
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to antihypertensive medication adherence among adults with intellectual and developmental disability

Abstract: Adults with intellectual or developmental disabilities often have hypertension and mental illness, and are prescribed medications for treatment. This study examined psychotropic medication adherence as a mediator between the association of residence type and antihypertensive medication adherence for adults with intellectual or developmental disabilities. We used Medicaid data of adults with intellectual or developmental disabilities who had hypertension and prescribed antihypertensive medication (N = 1,201) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Unfortunately, we have no data on medication adherence and errors, so we cannot discuss or compare these findings. Yet, studies have shown that people with intellectual disabilities living at home were more likely to have lower adherence (Resciniti et al, 2022) and that education and accessible materials may increase the medication self-management capacities (Sheerin et al, 2021). The educational and information materials that we use in the overall project 'SDM in medication use' will likely contribute to improvement of medication self-management capacities and the quality of support from their caregivers and pharmacists in medication adherence of consumers with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we have no data on medication adherence and errors, so we cannot discuss or compare these findings. Yet, studies have shown that people with intellectual disabilities living at home were more likely to have lower adherence (Resciniti et al, 2022) and that education and accessible materials may increase the medication self-management capacities (Sheerin et al, 2021). The educational and information materials that we use in the overall project 'SDM in medication use' will likely contribute to improvement of medication self-management capacities and the quality of support from their caregivers and pharmacists in medication adherence of consumers with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear need for further work to map co-occurrence of conditions to explore differential quality of life, morbidity and mortality outcomes. Strategies to prevent MLTC, including weight management (Ptomey et al, 2017; Patience, 2018) medication adherence (Resciniti et al, 2020) and early screening (Dunkley et al, 2017) are also important to prevent future complications.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low number of people with intellectual disability, autism, and vegetative states, we did not combine them with other groups because they have specific characteristics in medication utilization adherence. [18][19][20] All statistical analyses were conducted using Stata 15 (StataCorp). 21 We used P < .05 as the threshold of significance for all analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We combined hearing and verbal disabilities (hereafter, hearing/verbal disability) and combined facial, balance, and epilepsy disabilities to form the group of other disabilities. Despite the low number of people with intellectual disability, autism, and vegetative states, we did not combine them with other groups because they have specific characteristics in medication utilization adherence . All statistical analyses were conducted using Stata 15 (StataCorp) .…”
Section: Methodsmentioning
confidence: 99%